Pemahaman dan Implementasi Ajaran Susila dalam Bhagavadgita pada Generasi Hindu di Desa Parabu Kecamatan Lariang Kabupaten Pasangkayu Sulawesi Barat : Penelitian - Ketut Agus Murdiana, I; Made Sutarwiyanti, Ni; Sara Damayanti, Kd; Gede Eka Windu Saputra, I (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The current rise in crime, harassment, declining moral values, and promiscuity reflects a character crisis in Indonesia. Therefore, it is important to understand and apply the teachings of Susila, especially those derived from the Bhagavadgita. This study formulated two problems: how the understanding and implementation of the teachings of Susila in the Bhagavadgita among the younger generation of Hindus, and the obstacles they face in Parabu Village, Lariang District, Pasangkayu Regency, West Sulawesi. This formulation aims to determine the level of understanding and application of these teachings among the younger generation of Hindus in the area. The study used a qualitative approach with descriptive methods, utilizing constructivist and structuralist theories. Data were determined through purposive sampling, collected through observation, literature review, and interviews, and analyzed using qualitative descriptive techniques with formal and informal presentation. The results of the study indicate that the understanding and application of the teachings of Susila in the Bhagavadgita among the younger generation of Hindus in Parabu Village has been fostered since childhood through the teachings of Daiwa Sampad, Asura Sampad, and Catur Purusa Artha. The obstacles they face mainly come from their environment, such as promiscuity and the negative impact of digital technology.